2017
DOI: 10.11604/pamj.2017.26.133.8363
|View full text |Cite
|
Sign up to set email alerts
|

Kyste hydatique de la fosse cérébrale postérieure

Abstract: L'hydatidose est une parasitose cosmopolite endémique au Maroc. L'échinococcose cérébrale est rare représentant 1 à 2% de l'ensemble des hydatidoses de l'homme et la localisation auniveau de la fosse postérieure est exceptionnelle. Nous rapportons le cas d'un enfant âgé de 12 ansadmis pour syndrome d'hypertension intracrânienne évoluant depuis trois mois. La tomodensitométrie cérébrale a objectivé une formation kystique de la fosse postérieurene se rehaussant pas après injection du produit de contraste. L'inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Reviewing the literature over the past ten years up to date from 2008 till 2018, using pubmed searching engine we found that some geographical distribution of this disease mainly involving the Middle East and developing countries [14,16,17]. The majority of the reported cases are from Asia and Africa [12,13,15,18]. Clinical information was gathered on a summarized Table 1, obviously all the cases are children or young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the literature over the past ten years up to date from 2008 till 2018, using pubmed searching engine we found that some geographical distribution of this disease mainly involving the Middle East and developing countries [14,16,17]. The majority of the reported cases are from Asia and Africa [12,13,15,18]. Clinical information was gathered on a summarized Table 1, obviously all the cases are children or young adults.…”
Section: Discussionmentioning
confidence: 99%